A simple ICA-based digital image watermarking scheme - Nguyen, Thang Viet (2011)
In a digital watermarking scheme, it is not convenient to carry the original image all the time in order to detect the owner's signature from the watermarked image. Moreover, for those applications that require different watermark for different copies, it is preferred to utilize some kind of watermark-independent algorithm in extraction (does not need a priori knowledge of the watermark). In this paper we introduce a novel approach called WMicaT that employs an independent component analysis technique in watermark embedding and extraction. Using a single ‘public image’ that can be made publicly available, the new algorithm is able to extract the watermark without requiring the original image and any information about the watermark. In addition, the watermark is not limited to some specific binary sequences but can be any meaningful image. The WMicaT method, undergoing different experiments, has shown its robustness against many attacks.